Analysis of Moral Values in Princess Muslimah & 9 Characters of Great Leaders by Watiek Ideo and Niken Wulandari - Miftakhul Janah, Sinta (International Proceedings of Nusantara Raya, 2022)
Moral value is something that relates to individual human beings as a whole and totality. In storybooks, moral values ​​are usually intended as a means to relate to something that can be taken from stories related to problems that exist in real life. This study aims to analyze and describe the moral values ​​contained in the Storybook Princess Muslimah & 9 Characters of Great Leaders by Watiek Ideo & Niken Wulandari. This study uses a literature study by listening, recording and concluding and analyzing relevant references from various existing sources such as books, journals, articles and documents that are by the moral values ​​in the storybook. The results of this study indicate that the moral values ​​contained in the storybook Princess Muslimah & 9 Characters of Great Leaders by Watiek Ideo & Niken Wulandari are as follows: religious moral values ​​(thanks and giving thanks), social care moral values ​​(sharing, complementing each other, aware of actions), the moral value of honesty, the moral value of responsibility, the moral value of self-control, and the moral value of empathy.